Постать Олександра Кониського у публіцистиці Сергія Єфремова 1900 – 1919 років - Іваницька, С. (Сiверянський лiтопис, 2015)
Метою статті є аналіз публіцистичних текстів відомого літературознавця, критика, публіциста Сергія Єфремова (1876–1939), в яких відбився процес меморіалізації
образу громадського діяча та письменника О. Я. Кониського (1836–1900). Автор на
підставі теорії колективної пам’яті розглядає національну ліберально-народницьку
еліту як «уявлену спільноту», що задля формування власної ідентичності потребувала «винайдення традиції», творила «місця пам’яті», канонізувала «знакові» постаті українського руху. Археографічна частина роботи містить нотатки, некрологи, статті
й посвяти на честь Олександра Кониського, написані С. Єфремовим в 1900–1919 роках та опубліковані на шпальтах часописів «Літературно-науковий вістник», «Киевская газета», «Киевская старина», «Книгарь», газети «Рада». Целью статьи является анализ публицистических текстов известного литературоведа, критика, публициста Сергея Ефремова (1876–1939), в которых отразился
процесс мемориализации образа общественного деятеля и писателя А. Я. Конисского
(1836–1900). Используя теорию коллективной памяти, автор рассматривает национальную либерально-народническую элиту как «воображаемое сообщество», которое
для формирования собственной идентичности нуждалось в «изобретении традиций»,
творило «места памяти», канонизировало «знаковые» фигуры украинского движения.
Археографическая часть работы содержит заметки, некрологи, статьи и посвящения в честь Александра Конисского, написанные С. Ефремовым в 1900–1919 годах и опубликованные на страницах журналов «Литературно-научный вестник», «Киевская
газета», «Киевская старина», «Книгарь», газеты «Рада». The article aims is analyze of journalistic texts of known literary critic, journalist, public figure
Sergei Yefremov (1876-1939), which reflected of the process of creating a commemorative
image of the public figure and writer O. Y. Konysky (1836-1900). Author based on the theory
of collective memory examines national liberal-populist elite as «imagined community», which
for to form a collective identity is need of the «invention of tradition», of the creation «places of
memory» and the canonization «symbolic» leaders of the Ukrainian movement. Archeographic
part of this work contains notes, obituaries, articles in honor of Alexander Konysky, which S.
Yefremov written in the years 1900-1919 and published on the pages of magazines «Literary
and Scientific vistnyk», «Kievskaya Gazeta», «Kiev’s antiquity», «Knyhar», newspapers
«Rada». There are some conclusions that introduction of Yefremov’s journalistic heritage lets
to trace the process of designing by contemporaries of A. Konysky’s image, give new arguments
on specificity and interpretation of results of his work. S. Yefremov pointed of O. Konysky’s
outstanding study of by Taras Shevchenko, considered him is the founder of this literary research
direction, called one of the «recognized masters of fiction», had seen confrontation O. Konysky
and M. Dragomanov. The policy of national culture, «the battle for history», differentiation
own and other people’s experience, awakening civil society, personal responsibility of the ideas
and actions, the actual combination of the slogans of national liberation and social justice is
a list of problems that are solved for its activities A. Konysky (to 1900) and S. Yefremov (to
1920). Getting to know the Yefremov’s journalism texts can trace the metamorphosis memorial
Konysky’s image of the in the context of space-time transformations.